HUBUNGAN PEMBAKARAN DENGAN PADANG PENGGEMBALAAN DAN AKTIVITAS PERTANIAN DI NUSA TENGGARA TIMUR - Ferdinan S. Suek; Melkianus D.S. Randu (Politeknik Pertanian Negeri Kupang, 2010)
Burning Connection With Pasturing Field And Agriculture Activity At East Nusa Tenggara. Land use for agriculture in East Nusa Tenggara (NTT) is still using traditional pattern which was characterized by the very simple application of technology. To open new land, farmers are practising slash and burn system before sowing.Burning concept, involving the use of fire burning, is one concept among other concepts namely cultivation pattern, animal husbandry and others. These concepts are part of agriculture system for community in NTT. Community, with their own reasons and experiences besides physical and geographical environment, are using fire as an important component for their living agriculture.Controlled burning in the appropriate season is an effective way to improve pasture land. For example, burning at the end of the dry season can eradicate the old, dry and low nutritional value plants allowing young grass to grow at the beginning of the rainy season.From the socio-economic point of view, burning or fire technology is a relatively simple technology used by unskilled poor farmers. An arising issue is how to inform the farmers with burning technology to use fire in an efficient and effective way.Keywords: dry land, farming activity, burning